2015
DOI: 10.5090/kjtcs.2015.48.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Non-Small Cell Lung Cancer in Patients on Hemodialysis due to Chronic Kidney Disease: Clinical Outcome and Intermediate-Term Results

Abstract: BackgroundPatients on dialysis undergoing surgery belong to a high-risk group. Only a few studies have evaluated the outcome of major thoracic surgical procedures in dialysis patients. We evaluated the outcomes of pulmonary resection for non-small cell lung cancer (NSCLC) in patients on hemodialysis (HD).MethodsBetween 2008 and 2013, seven patients on HD underwent pulmonary resection for NSCLC at our institution. We retrospectively reviewed their surgical outcomes and prognoses.ResultsThe median duration of HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Dialysis patients were more likely than non-dialysis patients to develop adverse events within 30 days postoperatively (morbidity 28.6 vs 10.7%, respectively; P  < 0.001; mortality 12.7 vs 1.5%; P  < 0.001). Several small-scale studies [40–50] evaluated surgical risk associated with hemodialysis in patients undergoing pulmonary resection (Table 3), and a 2017 study of the Japan NCD clearly showed high mortality and morbidity in this population [1]. The small-scale studies showed that hyperkalemia was the most frequent complication after pulmonary resection (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dialysis patients were more likely than non-dialysis patients to develop adverse events within 30 days postoperatively (morbidity 28.6 vs 10.7%, respectively; P  < 0.001; mortality 12.7 vs 1.5%; P  < 0.001). Several small-scale studies [40–50] evaluated surgical risk associated with hemodialysis in patients undergoing pulmonary resection (Table 3), and a 2017 study of the Japan NCD clearly showed high mortality and morbidity in this population [1]. The small-scale studies showed that hyperkalemia was the most frequent complication after pulmonary resection (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…of ptsSurgical procedureApproachMorbidity (%)Ohta [40]19921PnOpen1 (100)Yamamoto [41]19961LbOpen1 (100)Tsuchida [42]20017LbOpen7 (100)Ciriaco [43]20056*Lb 5, Pn 1, Weg 1Open4 (57)Yajima [44]20051LbOpen1 (100)Obuchi [45]200911Lb 9, Pn 1, Weg 1VATS 4, Open 73 (27)Akiba [46]20102Lb 1, Wed 1VATS0 (0)Takahama [47]201024Lb 22, Sg 1, Weg 1Open13 (59)Matsuoka [48]20135Lb 4, Sg 1VATS2 (40)Caroli [49]20151LbVATS0 (0)Park [50]20157Lb 5, Weg 2VATS 4, Open 33 (42) No number, pts patients, Pn pneumonectomy, Lb lobectomy, Sg segmentectomy, Weg wedge resection*One patient had two operations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ESKD is not considered an absolute contraindication for tumor resection surgery. The 5‐year survival rate was 28% as compared to 47.5% in general population 67–69 . Post‐surgical outcomes in ESKD patients undergoing gastrectomy and hepatectomy for gastric and hepatocellular cancer, respectively, are not different from the general population , 70,71 .…”
Section: Surgery In Eskdmentioning
confidence: 90%
“…Evidence from small patient series shows that pulmonary resection for non-small cell lung cancer in patients receiving hemodialysis is associated with high rates of morbidity and mortality (75% and 10%, respectively) (Akiba et al 2010 ; Ciriaco et al 2005 ; Matsuoka et al 2013a ; Park et al 2015 ). Although radical lung resection appears to be safe in selected patients, careful metabolic, hematologic, and pharmacological management is mandatory during the perioperative period.…”
Section: Preadmission Carementioning
confidence: 99%